Literatur Review: Penerapan Senam Dismenore dalam Menurunkan Nyeri Menstruasi - Islami, Ica Maulina Rifkiyatul (Jurnal Keperawatan Profesional, 2023)
The pain that teenage daughters experience during menstruation is called menstruation. An imbalance of the hormone progesterone in the blood, prostaglandins, and stress or psychological factors are the causes of dysmenorrhea in some women. Unpleasant feelings characterized by agitation or tension as well as abnormal hemodynamic signs caused by stimuli in the sympathic, parasympathetic, and endocrine systems are known as anxiety. Menstrual cramps can be done to prevent this from happening. One method to cure dysmenorrhea is exercise. Your body produces endorphins during exercise. The brain produces these hormones to give a feeling of comfort and relaxation. The aim of this study is to find out how effective dysmenorrheic exercises are in reducing the pain and anxiety experienced by adolescents suffering from dysmenorrea. This research uses a literature review. Google Schoolar, Science Direct, PubMed, and Elsevier are used to search for articles. The research uses keywords like dimenore, adolescent, menstrual pain, dysmenore exercise. 5 selected articles that qualify for inclusion and discussion topics. In five journal studies it was found that dysmenorrheic exercise has the potential to reduce pain during menstruation.